2006
DOI: 10.1111/j.1365-2265.2006.02572.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density is not reduced in HIV‐infected Caucasian men treated with highly active antiretroviral therapy

Abstract: HIV-infected men treated with HAART are lighter than healthy controls. This weight difference is responsible for a small decrement in hip BMD. Overall, BMD is not significantly reduced in HIV-infected Caucasian men treated with HAART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 42 publications
(165 reference statements)
4
33
0
Order By: Relevance
“…Meanwhile, in a previous study we compared QUS BMD between HIV-1-infected patients and controls in Senegal and showed that HIV patients had a lower BMD, which was partly explained by lower BMI [8]. This report was consistent with several studies suggested that differences in BMI and body composition between HIV-1-infected and uninfected subjects may largely account for differences in BMD [21,22]. In contrast, a recent study conducted among 247 black South African women reported no difference in BMD DXA measurements by HIV infection status despite HIV positive women being lighter and with lower BMI [23].…”
Section: Discussionsupporting
confidence: 77%
“…Meanwhile, in a previous study we compared QUS BMD between HIV-1-infected patients and controls in Senegal and showed that HIV patients had a lower BMD, which was partly explained by lower BMI [8]. This report was consistent with several studies suggested that differences in BMI and body composition between HIV-1-infected and uninfected subjects may largely account for differences in BMD [21,22]. In contrast, a recent study conducted among 247 black South African women reported no difference in BMD DXA measurements by HIV infection status despite HIV positive women being lighter and with lower BMI [23].…”
Section: Discussionsupporting
confidence: 77%
“…27 None of the other recent datasets of HIV infected patients reporting a high prevalence of OP and progression to lower BMD was directly comparable to ours, as they did not share the same inclusion criteria and/or study design, none of them providing universal screening of BMD as the only criterion. 16,21,[24][25][26]28,29 Bonjoch et al, 26 for instance, found 47.5% of osteopenic and 23% of frankly osteoporotic patients among 671 selected HIV patients at increased risk of BMD loss, investigated by retrospective retrieval of DXA scan data. In a longitudinal assessment of BMD in HIV-infected women compared with uninfected controls, Dolan et al 16 found lower levels of BMD among HIV-infected patients and higher levels of osteocalcin and urine N-telopeptide of type 1 collagen, an observation confirmed at follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…The use of HAART and duration of use has been similar in HIV patients with normal and decreased BMD [4]. The decrease in weight and BMI in HIV patients may be more linked to the decreased BMD [31,36,37] than the use of HAART. Bone mineral density (BMD) and content (BMC) has been shown to remain stable for 2-6 years in adults [32][33][34] or even to increase [35] in adult patients mainly treated with HAART.…”
Section: Drugs Against Hivmentioning
confidence: 93%
“…However in vivo, evidence for a negative effect of HAART has been scarcer, and has so far been based on theoretical considerations [25]. In fact BMD has been shown to be stable and not significantly reduced in patients treated with HAART in many studies [4,[31][32][33][34][35][36][37][38][39]. The use of HAART and duration of use has been similar in HIV patients with normal and decreased BMD [4].…”
Section: Drugs Against Hivmentioning
confidence: 99%